Understanding Students’ Experiences with Intercultural Learning Materials for Drama Subject in Higher Education - Eripuddin Eripuddin; Pipit Rahayu; Evi Kasyulita (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students’ perception is highly important to evaluate the learning materials. The purpose of this study was to determine students' perceptions of using the intercultural learning material in the drama subject. The population of this research was the sixth-semester students of the English Department at Pasir Pengaraian University. The sample of this research was obtained by total sampling technique. The sample of this research was 34 students. The instrument of this research was the questionnaires; using the Likert scale. It was developed by using intercultural learning and perception. It was distributed to 34 students consisting of 28 female students and 6 male students. The data were analyzed by using a statistical package to find out the total perception of the students. The results showed that students had positive perceptions that were obtained from the three indicators, namely motivation, difficulties, and material efficacy of using intercultural learning material in the drama subject. The perception of motivation, difficulties, and material efficacy were categorized as positive perceptions. It has a percentage of 77.5%, 74.8%, and 75.8% for each indicator. Thus, intercultural learning material is effective learning material, especially in the drama subject.